Development of a robust optimization method for optimal operation of microgrids with electric vehicles and renewable energy resources - Zandrazavi, Seyed Farhad [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Microgrids can pave the way for the decarbonization of power systems by providing excellent infrastructure for the proliferation of distributed energy resources and electric vehicles. Nevertheless, in the presence of renewable energy generation and electric vehicles, the energy management of microgrids seems inseparable from uncertainties. On one hand, imperfect forecasts of intermittent renewable energy generation, electric load demand, and electricity price impose a high level of uncertainties in the daily optimal operation of microgrids. On the other hand, neglecting uncertainties by microgrids’ operators may lead to non-optimal solutions or even infeasible operational points. In order to mathematically model the optimal energy management of microgrids, firstly some fundamental concepts linked to mathematical optimization are briefly introduced, including local optimality, feasibility, convexity, linear programming, integer programming, mixed-integer linear programming, nonlinear nonconvex programming, and nonlinear convex programming. In addition, the power flow formulation in microgrids is extracted step by step, and then it is used to model deterministic energy management of microgrids as a nonlinear nonconvex programming problem. Then, relaxation and linearization are used to transform the aforementioned model into a convex model so as to guarantee the global optimality of the solutions. Secondly, to embrace uncertainty, the most well-known methods deployed widely in the literature for modeling uncertainty in the operation of microgrids are introduced and their characteristics are explained and compared. In order to model uncertainty in practice, a two-stage stochastic mixed-integer conic programming model is presented. Uncertainties linked to photovoltaic generation, wind power generation, electric demand, and electricity prices are included in the model via scenarios. It is noteworthy that the optimization models are developed in AMPL and solved via the CPLEX solver and tests are carried out on IEEE 33-bus and 69-bus test systems, to evaluate the effectiveness of the proposed models. The results show how considering the reconfigurability of microgrids can positively affect the operation by contributing to cost, voltage deviation and power loss reduction. Moreover, the results show considering scenarios can contribute to uncertainty modeling, yet it will affect the optimal solution compared to deterministic methods, as the constraints must be satisfied for every scenario, simultaneously.

As microrredes podem abrir caminho à descarbonização dos sistemas energéticos, fornecendo excelentes infraestruturas para a proliferação de recursos energéticos distribuídos e de veículos elétricos. No entanto, na presença da geração de energia renovável e de veículos elétricos, a gestão energética das microrredes parece inseparável das incertezas. Por um lado, as previsões imperfeitas da geração intermitente de energia renovável, da demanda da carga elétrica e do preço da eletricidade impõem um elevado nível de incertezas no funcionamento diário ótimo das microrredes. Por outro lado, negligenciar as incertezas por parte dos operadores de microrredes pode levar a soluções não ótimas ou mesmo a pontos operacionais inviáveis. A fim de modelar matematicamente o gerenciamento ótimo de energia de microrredes, inicialmente alguns conceitos fundamentais ligados à otimização matemática são brevemente introduzidos, incluindo otimalidade local, viabilidade, convexidade, programação linear, programação inteira, programação linear inteira mista, programação não linear não convexa e programação não linear convexa. Além disso, a formulação do fluxo de potência em microrredes é extraída passo a passo e então usada para modelar o gerenciamento determinístico de energia como um problema de programação não linear não convexo. Dessa forma, utiliza-se a relaxação e a linearização para transformar o referido modelo em um modelo convexo de forma a garantir a otimalidade global das soluções. Em seguida, para abranger a incerteza, são introduzidos os métodos mais conhecidos e amplamente utilizados na literatura para modelar a incerteza na operação de microrredes e as suas características são explicadas e comparadas. Para modelar a incerteza na prática, é apresentado um modelo de programação cônica estocástica inteira mista de dois estágios. As incertezas ligadas à geração fotovoltaica, geração de energia eólica, demanda elétrica e preços da eletricidade estão incluídas no modelo por meio de cenários. Vale ressaltar que os modelos de otimização são desenvolvidos em AMPL e resolvidos via solucionador CPLEX e testes são realizados em sistemas de teste IEEE de 33 barramentos e 69 barramentos, para avaliar a eficácia dos modelos propostos. Os resultados mostram como considerar a reconfiguração das microrredes pode afetar positivamente a operação, contribuindo para a redução de custos, desvios de tensão e perdas de energia. Além disso, os resultados mostram que a consideração de cenários pode contribuir para a modelagem da incerteza, mas afetará a solução ótima em comparação com métodos determinísticos, uma vez que as restrições devem ser satisfeitas para todos os cenários, simultaneamente.
Desenvolvimento de um método robusto de otimização para o funcionamento ótimo de micro-redes com veículos elétricos e recursos de energia renovável
Keywords: Convex optimization; Electric vehicles; Energy management; Microgrids; Renewable generation; Uncertainty modeling; Otimização convexa; Veículos elétricos; Gestão de energia; Microrredes; Geração renovável; Modelagem de incerteza